A new three-dimensional progressive damage model for fiber-reinforced polymer laminates and its applications to large open-hole panels. (29th September 2019) - Wei, Lixiao; Zhu, Wenqing; Yu, Zhongliang; Liu, Junjie; Wei, Xiaoding
Abstract: With fiber-reinforced Polymers (FRPs) widely used in aircraft, design and analysis of the mechanical performance and stability of structures and parts made of FRPs with various open-holes become very important. Currently, accurately predicting the failure patterns and ultimate strength of open-hole FRP structures remains very challenging. In this paper, a three-dimensional progressive damage model based on Puck's criterion on unidirectional FRP laminates has been developed. More importantly, a scaling algorithm that can differentiate the shear deformation modes and automatically modify the shear toughness has been proposed and implemented in the model. With this modified shear damage evolution law, our model accurately estimates the tensile strengths and captures the failure pattern of carbon fiber reinforced polymer (CFRP) panels consist of different stacking schemes with large open-holes in the middle. Furthermore, our model results point out that in panels of [ ± 45 ] 5 stacking scheme the inter-laminar stresses, although relatively small in magnitude, have a significant influence on the damage initiation locations.